Fibrous Aerogels with Tunable Superwettability for High-Performance Solar-Driven Interfacial Evaporation - Xu, Chengjian; Gao, Mengyue; Yu, Xiaoxiao; Zhang, Junyan; Cheng, Yanhua; Zhu, Meifang (Nano-Micro Letters, 2023)
Solar-driven interfacial evaporation is an emerging technology for water desalination. Generally, double-layered structure with separate surface wettability properties is usually employed for evaporator construction. However, creating materials with tunable properties is a great challenge because the wettability of existing materials is usually monotonous. Herein, we report vinyltrimethoxysilane as a single molecular unit to hybrid with bacterial cellulose (BC) fibrous network, which can be built into robust aerogel with entirely distinct wettability through controlling assembly pathways. Siloxane groups or carbon atoms are exposed on the surface of BC nanofibers, resulting in either superhydrophilic or superhydrophobic aerogels. With this special property, single component-modified aerogels could be integrated into a double-layered evaporator for water desalination. Under 1 sun, our evaporator achieves high water evaporation rates of 1.91 and 4.20 kg m−2 h−1 under laboratory and outdoor solar conditions, respectively. Moreover, this aerogel evaporator shows unprecedented lightweight, structural robustness, long-term stability under extreme conditions, and excellent salt-resistance, highlighting the advantages in synthesis of aerogel materials from the single molecular unit. Highlights: 1 Hybrid fibrous aerogels with tunable wettability from the same molecular unit of vinyltrimethoxysilane are successfully developed. 2 Superhydrophobic and superhydrophilic hybrid aerogels are integrated into a double-layered evaporator, showing robust interfacial networks to withstand repeated and tremendous compression for 1000th cycle. 3 The evaporator delivers high water evaporation rates of 1.91 kg m−2 h−1 under laboratory conditions and 4.20 kg m−2 h−1 under outdoor experiments with the aid of wind (1 sun), enabling efficient salt rejection under continuous operation.